2014
DOI: 10.1371/journal.pone.0093630
|View full text |Cite
|
Sign up to set email alerts
|

On the Status and Comparison of Glucose Intolerance in Female Breast Cancer Patients at Initial Diagnosis and during Chemotherapy through an Oral Glucose Tolerance Test

Abstract: AimsThis study is to estimate the status and comparison of glucose intolerance in female breast cancer patients at initial diagnosis and during chemotherapy through an oral glucose tolerance test (OGTT), as well as to learn the effect of chemotherapy on the glucose metabolism of breast cancer patients.MethodsAll the 79 breast cancer patients at initial diagnosis, with the mean age of 53.2 years, and 96 breast cancer patients before the 5th or 6th cycle of chemotherapy, with the mean age of 51.5 years, particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…High fat and carbohydrate diets, associated with dietary carcinogenesis, contribute to abnormal glucose tolerance and cancer 1 , 2 . Previous studies suggest that metabolic syndrome is associated with a modestly increased risk of second breast cancer events and breast cancer-specific mortality 3 .…”
Section: Introductionmentioning
confidence: 99%
“…High fat and carbohydrate diets, associated with dietary carcinogenesis, contribute to abnormal glucose tolerance and cancer 1 , 2 . Previous studies suggest that metabolic syndrome is associated with a modestly increased risk of second breast cancer events and breast cancer-specific mortality 3 .…”
Section: Introductionmentioning
confidence: 99%
“…We must point out that in breast cancer survivors, impaired fasting glucose increases the risk of developing type 2 diabetes mellitus, and the coincidence of type 2 diabetes mellitus with inadequate metabolic control increases cancer recurrence and mortality. [89] In addition, impaired fasting glucose increases the risk of other new carcinomas and all-cause mortality. [121314] These circumstances are significant because the number of breast cancer survivors is rising worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Besides, in these survivors, impaired fasting glucose is a high-risk factor to develop type 2 diabetes mellitus. [8] Women with advanced breast cancer and type 2 diabetes mellitus had bigger possibilities of cancer recurrence. [9]…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have addressed glycaemic control after treatment in patients with other types of cancer. A small cross‐sectional study of Chinese women with breast cancer showed that the prevalence of diabetes and pre‐diabetes was statistically significantly lower in women undergoing chemotherapy than in women who had just been diagnosed with breast cancer . Although the causality cannot be established, and the study had methodological drawbacks related to the lack of comparative measures of glycaemic control for the same patients and the lack of control for changes in dietary factors before and during chemotherapy, the authors speculated that this could be the result of a decrease in diabetes‐inducing factors following from the cancer itself.…”
Section: Reverse Causation and Common Originmentioning
confidence: 99%